2013
DOI: 10.1209/0295-5075/104/35002
|View full text |Cite
|
Sign up to set email alerts
|

THz generation by cosh-Gaussian lasers in a rippled density plasma

Abstract: This paper presents a scheme to achieve THz radiation by the beating of cosh-Gaussian lasers in spatially periodic density plasma (ripple density). Here, the lasers exert a nonlinear ponderomotive force along the transverse direction which imparts an oscillatory velocity to electrons that couples with the density ripple to generate a stronger transient transverse current due to the spatial variation of their fields, driving THz radiation. The importance of laser-beam-width parameters, decentred parameter, ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…The role of density ripple in the plasma in THz generation has been discussed by several researchers Singh et al, 2013). The importance of density ripple in the plasma has also been discussed by some authors in context of other phenomena taking place in the laser-plasma interaction (Singh et al, 2010;Xia & Xu, 2013;Xia, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of density ripple in the plasma in THz generation has been discussed by several researchers Singh et al, 2013). The importance of density ripple in the plasma has also been discussed by some authors in context of other phenomena taking place in the laser-plasma interaction (Singh et al, 2010;Xia & Xu, 2013;Xia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…have been used to generate THz Singh et al, 2013). As the propagation and focusing properties of Gaussian laser beam in plasma have been studied extensively (Sodha et al, 1974;1979), it is one of the most preferred beam profiles used in laser-plasma interaction studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] Vacuum electronic sources include the backward-wave oscillator, [49,50] extended-interaction klystrons, [51,52] travelling-wave tubes, [53] and synchrotrons. [66] Varshney et al have proposed THz radiation by beating of two cosh-Gaussian lasers in a rippled density plasma in the presence of a transverse static magnetic field. [58,59] Frequency multipliers are used to fundamentally shift sub-THz electronic oscillations into the THz range.…”
Section: Introductionmentioning
confidence: 99%
“…[62,63] Another way to generate THz radiation is to use semiconductor superlattice. [73] Many cited references [30,31,38,[65][66][67] study THz radiation generation by beating of two laser beams by applying a perpendicular magnetic field to the laser beams' propagation direction to achieve higher efficiency than if they have used different laser beam profile. [65] Singh et al have reported THz generation by mixing two cosh-Gaussian laser beams in a density rippled plasma.…”
Section: Introductionmentioning
confidence: 99%